Implementation of Organizing Function in Academic Administration Management by the Head of MIS At-Taqwa Sambas - Andi Kurniawan; Arnadi; Wulan Purnamasari (Departement Of Master Of Islamic Education Graduate Programme Sultan Muhammad Syafiuddin Institute Of Islamic Studies Sambas, Indonesia, 2022)
This study focuses on the implementation of management functions in academic administration carried out by the Head of MIS At-Taqwa Sambas in the 2020/2021 academic year, especially the organizing function. This research is a qualitative research with a descriptive approach. Data collection methods in the form of field observations, interviews, and documentation. The results of the study indicate that there are two activities that are a form of implementing the organizational function in academic administrative management carried out by the Head of MIS At-Taqwa Sambas, namely forming the organizational structure of the madrasa and dividing the duties of teachers and madrasa employees. The implementation of the organizing function is carried out in accordance with the Islamic perspective by referring to the Al-Qur'an Surah Ash-Shaff Verse 4 which contains three principles, namely cohesiveness in one command, working together on good things, and division of tasks according to expertise.